Integrating SEI into Layered Conductive Polymer Coatings for Ultrastable Silicon Anodes. Issue 31 (30th June 2022) - Pan, Siyuan; Han, Junwei; Wang, Yiqiao; Li, Zhenshen; Chen, Fanqi; Guo, Yong; Han, Zishan; Xiao, Kefeng; Yu, Zhichun; Yu, Mengying; Wu, Shichao; Wang, Da‐Wei; et al.
Abstract: Tackling the huge volume expansion of silicon (Si) anode desires a stable solid electrolyte interphase (SEI) to prohibit the interfacial side reactions. Here, a layered conductive polyaniline (LCP) coating is built on Si nanoparticles to achieve high areal capacity and long lifespan. The conformal LCP coating stores electrolyte in interlamination spaces and directs an in situ formation of LCP‐integrated hybrid SEI skin with uniform distribution of organic and inorganic components, enhancing the flexibility of the SEI to buffer the volume changes and maintaining homogeneous ion transport during cycling. As a result, the Si anode shows a remarkable cycling stability under high areal capacity (≈3 mAh cm −2 ) after 150 cycles and good rate performance of 942 mAh g −1 at 5 A g −1 . This work demonstrates the great potential of regulating the SEI properties by a layered polymer‐directing SEI formation for the mechanical and electrochemical stabilization of Si anodes. Abstract : A layered conductive polyaniline (LCP) coating is built from a bottom‐up polymer design strategy for Si anodes. The in situ formation of LCP‐integrated solid electrolyte interphase (SEI) with uniform structure and flexible mechanical property enhances the stability of the electrode–electrolyte interface.